SPE California Regional Meeting 1977
DOI: 10.2118/6523-ms
|View full text |Cite
|
Sign up to set email alerts
|

A Caustic Steamflood Pilot-Kern River Field

Abstract: From October 1973 to June 1976 a caustic steamfloodpilot test projectwas operatad in the Kern River Field of California. The test was conductedin nine adjscent five-spot patternsand utilized Sodium Hydroxideas an additive to the injected steam.The purpose of this paper :[sto present and discuss the operationand rasults of the pilot project. Initial researchand planning processesare descrtbed in addition to comparison of the pilot productionresponsewith other similar patterns in the same area of the field.Trace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1982
1982
2013
2013

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Another field trial of caustic with steam was reported by Robinson et ai. 9 IFT between the three alkaline solutions and an acidic oil have been completed for temperatures up to 356°F [l80°C]. For these measurements, the effects of salt, surfactant, and alkali content of the solutions were studied at elevated temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Another field trial of caustic with steam was reported by Robinson et ai. 9 IFT between the three alkaline solutions and an acidic oil have been completed for temperatures up to 356°F [l80°C]. For these measurements, the effects of salt, surfactant, and alkali content of the solutions were studied at elevated temperatures.…”
Section: Introductionmentioning
confidence: 99%